2017
DOI: 10.1111/jsr.12641
|View full text |Cite
|
Sign up to set email alerts
|

Reestablishment of individual sleep structure during a single 14‐h recovery sleep episode after 58 h of wakefulness

Abstract: Sleep structure is highly stable within individuals but different between individuals. The present study investigated robustness of the individual sleep structure to extended total sleep deprivation. Seventeen healthy men spent a baseline night (23:00-07:00 hours), 58 h of sleep deprivation and a 14-h recovery night (17:00-07:00 hours) in the laboratory. Intraclass correlation coefficients showed that the agreement between baseline and recovery with respect to the proportion of the different sleep stages incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Key changes are also observed during the N2 and N3 stages. Longer periods of RS result in a more similar proportion of time spent in sleep stages between normal sleep and RS [29]. Therefore, we speculate that individuals experienced increases in the proportion of SWS during RS, relative to the amount observed during normal sleep.…”
Section: Behavioral Performancementioning
confidence: 83%
See 2 more Smart Citations
“…Key changes are also observed during the N2 and N3 stages. Longer periods of RS result in a more similar proportion of time spent in sleep stages between normal sleep and RS [29]. Therefore, we speculate that individuals experienced increases in the proportion of SWS during RS, relative to the amount observed during normal sleep.…”
Section: Behavioral Performancementioning
confidence: 83%
“…Interestingly, it is the intensity rather than the duration of sleep that in uences the recovery of function following SD. Sleep intensity during SWS is regarded as an indicator of homeostatic sleep stress [29,60]. After one night of SD, less than 10 h of RS can su ciently decrease the level of sleep stress to that observed at the end of a typical 8-h period of normal sleep [61,62].…”
Section: Behavioral Performancementioning
confidence: 99%
See 1 more Smart Citation
“…, 2009). Regarding recovery, a recent international multi-collaborative study demonstrated the need for a minimum of 14 hours of continuous sleep to recover to a normal neurophysiological sleep pattern following 58h of sleep deprivation (Hennecke et al, 2019). If this does not occur, the damage increases proportionally.…”
mentioning
confidence: 99%
“…Hennecke et al. () present an interesting experimental study investigating 17 young healthy men before and after 58 hr of wakefulness and during 14 hr of recovery sleep. Their main finding from their data analysis refers to individual sleep structure during baseline sleep and during 14 hr of recovery sleep.…”
mentioning
confidence: 99%